Objectives of sustainable development of Ukraine and nature management: actual problems of achieving balancing processes of use and reproduction of natural resources - Duliba, Yevheniia; Melnyk, Oleh; Zlenko, Anna; Duraeva, Natalia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The article investigates the relevant problems of Ukraine in the field of protection and protection of the environment when implementing the goals of sustainable development of Ukraine.The current state of nature management in Ukraine is outlined. It is noted that Ukraine belongs to a group of countries with complex environmental problems.The reasons that led to the emergence of environmental problems and to a satisfactory state of implementation of state environmental policy: the subordination of environmental priorities of economic expediency; the predominance of resource and energy-intensive industries in the structure of the economy, mostly negative environmental impact, which is significantly increased due to the non-regulatory legislation when moving to market conditions; physical and moral demolition of fixed assets in all branches of the national economy; ineffective system of public administration in the field of environmental protection and regulation of the use of natural resources, unsatisfactory level of compliance with environmental legislation and environmental rights and duties of citizens; unsatisfactory control over the observance of environmental legislation and the disadvantage of the inevitability of responsibility for its violation; insufficient funding from state and local budgets of environmental measures, financing of such measures for residual principle.It is noted that the key to the effective sustainable development of Ukraine should be the formation of effective state environmental policy and its implementation. It is necessary to reform the normative principles of public administration in the field of natural resources.